Physiology Responses and Players’ Stay on the Court During a Futsal Match: A Case Study With Professional Players - Dos-Santos, Julio Wilson; da Silva, Henrique Santos; da Silva Junior, Osvaldo Tadeu; Barbieri, Ricardo Augusto; Penafiel, Matheus Luiz; da Silva, Roberto Nascimento Braga; Milioni, Fábio; Vieira, Luiz Henrique Palucci; Coledam, Diogo Henrique Constantino; Santiago, Paulo Roberto Pereira; Papoti, Marcelo (Frontiers in Psychology, 2020)
Physiological responses in futsal have not been studied together with temporal information about the players' stay on the court. The aim of this study was to compare physiology responses of the heart rate (HR) and blood lactate concentration ([La-]) between 1-H and 2-H considering the time of permanency of the players on the court at each substitution in a futsal match. HR was recorded during entire match and [La-] was taken after each substitution in seven players. %HRmean (89.6 ± 2.3 vs 88.0 ± 5.0 %HRmax) and [La-]mean (8.5 ± 3.0 vs 8.2 ± 3.0 mmol∙L-1) did not differ between 1-H and 2-H (effect size 0.0-0.4, trivial – small). Time in five intensity zones of 50-100 %HRmax differed only in 60-70 %HRmax (p = 0.02). Coefficient of variation of the HR throughout the match was low (7%) and among the four outfield players on the court (quartets, 5%). Substitutions (2 player’s participation in each half), time of permanence on court (7.1 ± 2.4 vs 9.5 ± 3.8 min), ratio between time in- and out- ratio on court (In:Outcourt = 1:1.3 ± 1:0.5 vs 1:1.0 ± 1:0.6 min) also were similar between 1-H and 2-H. Balancing the number of substitutions, and the In:Outcourt ratio of players in both halves of the match, time on the court of 8 min, made it possible to maintain intensity of the match in 2-H similar to the 1H. These results are a good guidance to coaches and for application in future studies.